(untitled) (Research, Society and Development, 2022)
Medicinal plants accumulate heavy metals and metalloids in their structure and in their secondary metabolites. However, when the population consumes these plants for the treatment or prevention of different diseases without proper quality control and quantification of heavy metals, they may be exposing themselves to toxicity risks due to the ingestion of chemical elements that are above the safe limits for human consumption. This narrative review study aimed to describe the regulations relating to the control of heavy metals in medicinal plants and herbal medicines, as well as highlighting the risks of heavy metals quantified in medicinal plants with emphasis on the species included in the List of Medicinal Plants of Interest to the Unified System of Brazilian Health (RENISUS), which have Systematized Information. According to the results obtained, the Systematized Information from RENISUS does not consider the information related to heavy metals and metalloids in medicinal plants, although there are published data. In this sense, we emphasize that it is necessary to periodically monitor heavy metals and inspect medicinal plants in the form of plant drugs, in order to mitigate the vulnerability of the population that consumes these products seeking health benefits based on herbal medicine.